Alternatives to criminal procedure against juvenile and young adult offenders and alternative to criminal procedure in the cases of domestic violence - Cvjetko Božica (Temida)
In the paper, the author is analyzing the Act on juvenile courts of the Republic of Croatia, which foresees a broad possibility of implementing the principle of opportunity in the pre-trial, i.e. reinvestigation phase of the procedure in terms of the decision of the public prosecutor about the criminal charge against these persons, including the implementation of particular obligations as informal sanctions. Particular attention is paid to the special obligation called off-court agreement. The aim of the off-court agreement is “reconciliation between the juvenile or young adult offender and the victim of the crime, and establishment of the social peace”. Similar project and the implementation of the principle of opportunity is used in the cases of the criminal offence of domestic violence. The main aim of these obligations is to offer professional assistance to the families which are in crisis and have difficulties related to the violent behavior of one family member - mostly the father. Such an approach is more efficient than the long lasting criminal procedure, testifying and strengthening the crisis in the family. This paper gives also an insight into the legal provisions concerning this measure and its implementation in practice.